A rare cause of neonatal hypoglycemia in two siblings: TBX19 gene mutation - Unal, Edip; Yildirim, Ruken; Tas, Funda Feryal; Tekin, Suat; Sen, Askin; Haspolat, Yusuf Kenan (Springer, 2018)
Congenital isolated adrenocorticotropic hormone (ACTH) deficiency (IAD) is a rarely seen disease characterized by low serum ACTH and cortisol levels accompanied by normal levels of the other anterior pituitary hormones. In these patients, severe hypoglycemia, convulsions, and prolonged cholestatic jaundice are expected findings in the neonatal period. In this paper, we present two siblings with TBX19 gene mutation. The first case was investigated at the age of 2 months for severe hypoglycemia, recurrent convulsions, and prolonged cholestatic jaundice persisting since the neonatal period. The second sibling presented with hypoglycemia in the neonatal period. In both cases, baseline cortisol and ACTH levels were low and cortisol response to the low-dose ACTH test was inadequate, while an other anterior pituitary hormones were normal. Thus, IAD was suspected. Genetic analysis of the TBX19 gene was performed. Both cases were homozygous for c.856 C>T (p.R286*), and hydrocortisone treatment was initiated. The first patient did not attend the clinic regularly. On attendance at another hospital, hydrocortisone treatment was discontinued and antiepileptic treatment was initiated because of suspected epilepsy. This led to developmental delay, measured with the Denver Developmental Screening Test II (DDST-II), because of cessation of the hydrocortisone therapy. The second sibling had normal development, as measured with the DDST. In conclusion, TBX19 gene analysis must be performed if adrenal insufficiency is associated with isolated ACTH deficiency. Delay in diagnosis may lead to inappropriate diagnoses, such as epilepsy, and thus inappropriate therapy, which may result in neonatal mortality.
Keywords: Adrenal insufficiency; TBX19 gene; Hypoglycemia; Isolated ACTH deficiency